Optimization of Zakat Funds in Improving Human Resource Quality: A Sharia Compliance Perspective at the Asia Moslem Charity Foundation - Ishmah Afiyah; Saif Uddin Ahmed Khondoker; Neil C. Cranston; Amrin (Demak Universal Journal of Islam and Sharia, 2025)
Objective: This study aims to analyze the optimization of zakat, infaq, and sadaqah (ZIS) funds in improving human resource quality at the Asia Moslem Charity Foundation (YAM). The foundation focuses on managing ZIS funds to support various social programs, particularly in enhancing education and human resource capacity. Proper allocation of ZIS funds can significantly contribute to improving educational quality and the effectiveness of human resource development in the community. Theoretical Framework: The theoretical framework of this study is based on the principles of Islamic philanthropy and Shariah compliance, emphasizing the effective and transparent distribution of zakat funds for socio-economic development. Literature Review: Literature review findings highlight that previous studies have extensively discussed the role of zakat in poverty alleviation and economic empowerment but have not thoroughly explored its impact on human resource development within Islamic foundations. Methods: This research adopts a qualitative approach using a case study method. Data collection involved in-depth interviews with foundation managers, teachers, and beneficiaries, as well as document analysis related to ZIS fund management at YAM. Additionally, an evaluation of human resource programs funded by ZIS was conducted to determine their contribution to education and workforce development. Results: The results indicate that ZIS funds at YAM have been effectively utilized to support various educational programs, such as scholarships for underprivileged students, procurement of educational facilities, and teacher training. In the field of human resource development, ZIS funds have also been used for community-based training, digital skills development, and da’i (Islamic preacher) training. However, challenges remain, particularly regarding transparency in fund management and the need for improved coordination between divisions. Implications: The implications of this study emphasize the importance of strengthening financial accountability and strategic planning in ZIS fund distribution to enhance human resource quality. Novelty: The novelty of this research lies in its in-depth analysis of the integration between ZIS fund management and strategies to improve human resource capacity within Islamic foundations. This study also provides practical recommendations for ZIS fund managers to enhance the effectiveness of fund allocation, ensuring broader social welfare impacts.